Serum Sickness-Like Reaction in Children: Review of the Literature - Blanca R. Del Pozzo-Magaña; Alejandro Lazo-Langner (European Medical Journal, 2019)
Serum sickness-like reaction (SSLR) is an acute inflammatory condition affecting children and adults characterised by the development of erythematous skin lesions and joint swelling with or without fever. Although these features resemble the ones seen in patients with classic serum sickness, the precise pathophysiology of SSLR remains unclear. It is considered that drugs, usually β-lactam antibiotics, and some infectious agents can trigger an immunologic reaction that leads to these clinical manifestations. This condition is usually under-recognised or mistakenly diagnosed as other conditions (e.g., urticaria, urticaria multiforme, reactive arthritis, erythema multiforme) and therefore infrequently reported. Until now, there was no standardised treatment for this condition and controversy regarding the use of antihistamines, nonsteroidal anti-inflammatory drugs, and oral corticosteroids remains. Most of the current literature on SSLR is based on occasional case reports series. The main objective of this manuscript is to offer an organised and updated review of the clinical features and current treatment options for paediatric SSLR, useful for physicians and other health professionals with interest in paediatrics and adverse drug reactions.